Preparation of Osteoporotic Women in Menopause for Dental Implantation and Prevention of Early Complications - Nodira G’.Achilova (American Journal of Biomedicine and Pharmacy, 2026)
Frequent referral of elderly patients, especially women, for removal of dental defects with the use of implants makes this problem especially important because asymptomatic, inconspicuous course of osteoporosis can be the cause of complications during treatment with the use of intraosseous implants.